Eosinophil recruitment is dynamically regulated by interplay among lung dendritic cell subsets after allergen challenge - Shuying Yi (Nature Portfolio, 2018)
Eosinophils are important mediators of allergic responses, but how they are recruited to the inflamed site is still unclear. Here the authors show that CD103+ cDC1 cells secrete CCL17 and CCL22 for eosinophil recruitment, with this process promoted by CD24−CD11b+ DC2s in the early phase but suppressed by CD24+ cDC2s in the late phase.